Concepts, measures and indicators of urban value in the City of Johannesburg: a GIS study using 2018 data - Weakley, Dylan (My University, 2022)
The value that cities provide to their citizens is not equally enjoyed by all, and this inequality is spatially represented. Urban value is a useful lens through which to analyse cities, towards making them more liveable and equal. Urban value in this work considers the spatial factors that attract people to live in different parts of cities, and from which they derive some form of value. Value, and urban value are complex concepts, however. Value may be social, environmental, experiential and many more, but is most commonly expressed in financial terms (exchange value). This can lead to negative outcomes in cities, especially in the context of the inequality many, such as Johannesburg face. This work assesses and compares three datasets from 2018 representing different types of or approaches to urban value in the City of Johannesburg (CoJ). The CoJ Valuation Roll represents exchange value, while the Gauteng City-Region Observatory’s Quality of Life (QoL) Survey and the City of Johannesburg’s Nodal Review Urban Potential Model represent social, environmental and place value. The work uses a literature review to define the theoretical framework and approach and spatial statistics and analysis to compare the datasets or representations of urban value. Hedonic spatial regression is used to determine the spatial factors that influence sectional scheme residential property price and quality of life scores in the CoJ. Visual analysis, statistical comparisons for correlation and clustering and an overlay analysis is then used to compare the three sources of data. The work finds that as population density increases, sectional scheme property price decreases, a positive finding for the City of Johannesburg’s spatial policies which revolve around the idea of densification. Less positive is that as population density increases, Quality of Life index scores decrease, highlighting the importance of integrated and considered approaches to urban densification. The qualitative analysis comparing the three datasets shows how they do not corelate perfectly and are differently distributed across space. It shows the complexity of a concept such as urban value, that can differ substantially when looked at from different perspectives. The work puts forward a novel way to map the CoJ valuation roll using Thiessen Polygons, that would be useful to the CoJ administration. Lastly, the work creates two overlay maps that are useful to housing developers and could lead to improved development outcomes for the CoJ. They show areas of high housing potential but with low property values that could promote social returns, financial feasibility and more affordable housing in the City.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in GIS and Remote Sensing to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, 2022